Method for manufacturing grain-oriented electrical steel sheet and grain-oriented electrical steel sheet
The method for manufacturing directional electromagnetic steel sheets involves using specific elements and induction heating techniques to maintain a lower slab temperature, addressing the challenges of abnormal grain growth and defects, and achieving superior magnetic properties and manufacturing efficiency.
Patent Information
- Application Number
- JP2023516825
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-29
- Filing Date
- 2022-10-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-10-31
AI Technical Summary
The challenge is to manufacture directional electromagnetic steel sheets with high inhibitor suppression force and excellent magnetic properties while reducing the heating temperature of the slab to prevent abnormal grain growth and defects in secondary recrystallization.
The method involves using a steel slab with elements like P, As, and Sb in specific ranges, and employing induction heating to maintain the slab temperature below 1380°C. The heating pattern includes a monotonic reduction in average current and a frequency range of 20Hz to 1000Hz during induction heating. This is followed by hot rolling, annealing, and multiple cold rolling steps with intermediate annealing to achieve the desired microstructure.
This approach effectively suppresses ear cracking and enhances manufacturing efficiency, achieving high magnetic flux density and improved iron loss characteristics in the directional electromagnetic steel sheets.
Smart Images

Figure 0007662031000010 
Figure 0007662031000011 
Figure 0007662031000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a grain-oriented electrical steel sheet and to a grain-oriented electrical steel sheet produced by the method. [Background technology]
[0002] Grain-oriented electrical steel sheets are primarily used as materials for the iron cores inside transformers, and there is a demand for low core loss in order to improve the energy usage efficiency of transformers. Here, methods for reducing the iron loss of grain-oriented electrical steel sheets include increasing the resistivity of the steel sheet itself, increasing the tension of the coating, and thinning the steel sheet, as well as surface treatment of the steel sheet and the {110} orientation of the crystal grains. <001> One method is to sharpen the crystal orientation to the Goss orientation. As an index of magnetic properties, the iron loss W per 1 kg of steel sheet when magnetized to 1.7 T in an AC magnetic field with an excitation frequency of 50 Hz is 17 / 50 In particular, the magnetic field strength, which is an indicator of the sharpening of the crystal orientation to the Goss orientation: magnetic flux density B at 800 A / m 8 is mainly used.
[0003] In order to sharpen the crystal orientation to the Goss orientation, that is, to increase the concentration of the Goss orientation, it is important to create a grain boundary mobility difference so that only the sharp Goss orientation grains grow preferentially, that is, to form the texture of the primary recrystallized plate into a specified structure, and to suppress the growth of recrystallized grains other than those with the Goss orientation by using precipitates called inhibitors.
[0004] As a technique using such an inhibitor, for example, Patent Document 1 discloses a method using AlN and MnS, and Patent Document 2 discloses a method using MnS and MnSe, both of which have been put into industrial use.
[0005] It is preferable that these inhibitors are uniformly and finely dispersed in the steel, so that in order to utilize the inhibitors, the slab is generally heated to 1300°C or higher before hot rolling to bring the inhibitor components into solution, and then the inhibitors are finely precipitated in the subsequent process. For example, in the method disclosed in Patent Document 3, Al is added to steel, and after hot rolling, the steel is annealed at 750 to 1200°C, and then rapidly cooled to precipitate fine AlN, thereby obtaining an extremely high magnetic flux density.
[0006] Furthermore, induction heating is useful for heating slabs to high temperatures, and several techniques have been proposed so far. For example, Patent Document 4 shows that induction heating can be used to increase the temperature to a range of 1150°C to 1250°C in order to shorten the time that slabs for grain-oriented electrical steel sheets are left in the furnace and reduce material variation. Patent Document 5 discloses a technique for minimizing desorption of Bi elements by adjusting the soaking time according to the soaking temperature. Patent Document 6 shows that when a slab is heated to a high temperature of 1400°C to 1470°C, by changing the frequency of the induction heating from 30 Hz to 300 Hz, heat removal from the slab surface can be enhanced and the generation of surface defects such as surface grain boundary oxidation can be suppressed.
[0007] Here, the high temperature heating of the slab plays a role of solutionizing the inhibitor required for the occurrence of secondary recrystallization in the grain-oriented electrical steel sheet, and in this respect, a higher heating temperature is preferable. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Special Publication No. 40-15644 [Patent Document 2] Special Publication No. 51-13469 [Patent Document 3] Special Publication No. 46-23820 [Patent Document 4] Patent No. 4389553 [Patent Document 5] Patent No. 3527309 [Patent Document 6] Special Publication No. 7-26156 Summary of the Invention [Problem to be solved by the invention]
[0009] However, when the heating temperature is high, abnormal grain growth of the crystal grains of the slab tends to occur, promoting the formation of coarse structures. These coarse structures are not sufficiently refined even in the subsequent hot rolling and cold rolling annealing processes, which can cause secondary recrystallization defects.
[0010] The inventors have conducted investigations into a method for producing a grain-oriented electrical steel sheet that maintains a high inhibitor suppression ability and has excellent magnetic properties even when the heating temperature of the slab is reduced below that of conventional methods. First, the reduction of inhibitor constituent elements Mn, S, Al, and N was examined by comparing the amounts of conventional components shown in, for example, Patent Document 6, but because the amount of inhibitor precipitated was reduced, the inhibitory power was reduced and only inferior magnetic properties were obtained after secondary recrystallization. Therefore, we searched for elements that do not form precipitates and are effective in increasing the inhibitory power in a solid solution state, and came up with the use of Group 15 elements including grain boundary segregation elements such as P and Sb. For example, the effect of adding Sb is disclosed in JP-B-2-115319. As a result, it was found that by setting the composition of the slab within the range described below, the inhibitor can be put into solution even if the heating temperature of the slab is reduced below the conventional level, and a high inhibitor suppressing effect can be exhibited in the subsequent process.
[0011] However, when grain-oriented electrical steel sheets were produced using this composition system, a problem emerged in which sheet breakage frequently occurred when the steel sheets after secondary recrystallization were subjected to flattening annealing. When the steel sheets passing through the flattening annealing line were observed in detail, cracks running in the width direction over several mm to several cm were formed at the width direction ends of the steel sheets. It was then discovered that sheet breakage easily occurred starting from these cracks.
[0012] Furthermore, they found that the cracks formed at the width direction edges of the steel sheet were already present at the time of hot rolling, and tended to grow and form after cold rolling. As is known for P, the Group 15 elements contained in the steel sheet promote the embrittlement of the steel when dissolved in iron, which is thought to cause rough edges during rolling. A report showing that segregated elements cause noticeable rough edges is shown, for example, in JP-B-6-63031.
[0013] A technique for preventing rough ears is disclosed in Japanese Patent Application Laid-Open No. 2000-73120. However, such edge roughening prevention technology involves optimizing the finish annealing conditions, and does not actively utilize Group 15 elements such as P and Sb.
[0014] In other words, it has been difficult to completely suppress rough edges in steels that actively utilize Group 15 elements such as P and Sb. There are various theories about the mechanism of edge roughness, but one hypothesis is given in JP 2002-105537 A. It is as follows: "Edge cracks occur when tension acts on the plate end in the longitudinal direction (rolling direction) during hot rolling, and it is believed that precipitates and grain boundaries become the starting point of the cracks. When a slab is heated to a high temperature close to the melting point, if the heating rate is fast, the inclusions and precipitates reach a high temperature without being fully dissolved in the parent phase. As a result, the composition of the parts where the inclusions and precipitates exist and their surroundings differs locally from the parent phase, and therefore the melting points also differ. At this time, if the melting point becomes low, local liquefaction occurs. In this way, if the temperature is raised to a high temperature quickly, local liquefaction occurs, and these become the starting points of edge cracks, making edge cracks more likely to occur."
[0015] The present invention has been made in consideration of the above circumstances, and its object is to propose a method for producing a grain-oriented electrical steel sheet that is excellent in manufacturability and that suppresses the formation of rough edges during rolling while actively utilizing elements that are effective in increasing the inhibitory power of grain growth in a solid solution state, and a grain-oriented electrical steel sheet produced by this method. [Means for solving the problem]
[0016] The gist of the present invention is as follows. 1. A steel slab containing C: 0.030-0.085 mass%, Si: 2.00-4.50 mass%, Mn: 0.03-0.50 mass%, S: 0.0005-0.0300 mass%, sol.Al: 0.005 mass% or more and less than 0.025 mass%, N: 0.0030-0.0090 mass%, and at least one element selected from P, As and Sb in the range of 0.005-0.500 mass%, with sol.Al / N satisfying 1.7 or more and 3.0 or less, and the balance being Fe and unavoidable impurities, Heat the slab to the extraction temperature Tr (℃) of 1380℃ or less by induction heating, and then heat it up to Tr-10℃ In a heating process in which a temperature T satisfying the range of ≦T≦Tr+10°C is maintained for 5 minutes or more, the average current value flowing through the slab is monotonically decreased as the heating time progresses, and the induction heating frequency is in the range of 20 Hz to 1000 Hz, In the hot rolling in which the slab is finish-rolled to obtain a hot-rolled sheet, the rolling end temperature at at least one of the front end and the tail end of the hot-rolled sheet is set to 950°C or less, and the hot-rolled sheet is annealed by soaking at a temperature of 750°C to 1170°C for 5 seconds to 90 seconds to obtain a hot-rolled sheet annealed sheet, The hot-rolled annealed sheet is cold-rolled once or at least twice with intermediate annealing to obtain a cold-rolled sheet of final thickness, and the cold-rolled sheet is then subjected to primary recrystallization annealing and then secondary recrystallization annealing.
[0017] 2. The steel slab further comprises: Se: 0.0005 to 0.0200 mass%, Ni: 0.01 to 1.50 mass%, Cr: 0.03 to 0.50 mass%, Cu: 0.03 to 0.50 mass%, Sn: 0.005 to 0.500 mass%, Bi: 0.005 to 0.500 mass%, Mo: 0.005 to 0.100 mass%, B: 0.0002 to 0.0025 mass%, Te: 0.0005 to 0.0100 mass%, Zr: 0.001 to 0.010 mass%, Nb: 0.001 to 0.010 mass%, V: 0.001 to 0.010 mass% and Ta: 0.001 to 0.010 mass% 2. The method for producing a grain-oriented electrical steel sheet according to 1 above, comprising one or more selected from the group consisting of:
[0018] 3. The method for producing a grain-oriented electrical steel sheet according to 1 or 2 above, wherein the steel slab contains at least two elements selected from Sb, As and P in an amount of 0.001 to 0.100 mass% each.
[0019] 4. A method for producing a grain-oriented electrical steel sheet according to any one of claims 1 to 3, wherein in the heating step of the steel slab, the frequency of the induction heating at the end of heating is set to be higher than that at the start of heating, and is not reduced at least during heating.
[0020] 5. The method for producing a grain-oriented electrical steel sheet according to any one of items 1 to 4 above, wherein in the step of obtaining the hot-rolled sheet annealed, the sheet is additionally held at a temperature of 700°C or more and 900°C or less for a period of 5 seconds or more and 180 seconds or less.
[0021] 6. The method for producing a grain-oriented electrical steel sheet according to any one of the above items 1 to 5, wherein the heating temperature of the steel slab is 1350° C. or less.
[0022] 7. The method for producing a grain-oriented electrical steel sheet according to any one of the above items 1 to 6, wherein, prior to a first cold rolling applied to the hot-rolled and annealed sheet, 5 mm or more of the coil end is cut off and removed.
[0023] 8. The composition, by mass%, satisfies Si: 2.00 to 4.50 mass%, Mn: 0.03 to 0.50 mass%, and further contains at least one element selected from Sb, As, and P at 0.005 to 0.100 mass%, with the balance being Fe and unavoidable impurities. 8 A grain-oriented electrical steel sheet having a hardness of 1.94T or more and a thickness of 0.35mm or less, in which the number of rough edges (edge cracks) formed at the edges exceeding 3cm in the width direction of the sheet is 0.020 or less per 10m of steel sheet length.
[0024] 9. The grain-oriented electrical steel sheet further comprises: Ni: 0.01 to 1.50 mass%, Cr: 0.03 to 0.50 mass%, Cu: 0.03 to 0.50 mass%, Sn: 0.005 to 0.500 mass%, Bi: 0.005 to 0.500 mass%, Mo: 0.005 to 0.100 mass%, B: 0.0002 to 0.0025 mass%, Te: 0.0005 to 0.0100 mass%, Zr: 0.001 to 0.010 mass%, Nb: 0.001 to 0.010 mass%, V: 0.001 to 0.010 mass% and Ta: 0.001 to 0.010 mass% 9. The grain-oriented electrical steel sheet according to 8 above, containing one or more selected from the group consisting of:
[0025] 10. The grain-oriented electrical steel sheet according to 8 or 9 above, which contains at least two elements selected from Sb, As and P in an amount of 0.001 to 0.100 mass% each. Effect of the Invention
[0026] According to the present invention, it is possible to provide a grain-oriented electrical steel sheet with good manufacturability that actively utilizes precipitation inhibitors such as AlN and MnS in combination with solid solution elements of Group 15 such as P and Sb while suppressing edge cracking defects associated with the addition of such Group 15 elements, and a manufacturing method thereof. [Brief description of the drawings]
[0027] [Figure 1] FIG. 13 is a diagram showing the relationship between slab heating time and coil current. [Diagram 2] FIG. 13 is a diagram showing the relationship between the slab temperature measured by a radiation thermometer and time during heating of the slab. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The experiment that led to the development of the present invention will now be described. First, the following experiment was conducted to verify the effectiveness of changing the heating pattern when heating slabs for grain-oriented electrical steel sheets in an induction heating furnace in suppressing rough edges. <Experiment 1> Steel material (C: 0.050 mass%, Si: 3.40 mass%, Mn: 0.05 mass%, sol.Al: 0.014 mass%, N: 0.007 mass%, S: 0.020 mass%, Sb: 0.10 mass%) with the balance being Fe and unavoidable impurities was smelted and made into a steel slab, which was then heated in an induction heating furnace with a target extraction temperature of 1320°C. Figure 1 shows the current value flowing through the coil during heating.
[0029] The current flowing through such a coil is I, the condition where the current value is always constant (◇ in Figure 1), II, monotonically The three conditions were: III increasing condition (■ in Fig. 1), and II monotonically decreasing condition (◯ in Fig. 1). Here, the current value was calculated from the voltage value by measuring the change in the magnetic field around the conductive part by winding a coil around the conductive part that passes the voltage applied to the coil, and using the circuit parameters. The current value was calculated from the voltage value by the average value for 20 minutes from the start of heating, and the average value for 10 minutes every 10 minutes thereafter. If the change in the current value is within 3%, the current value was considered to be constant. Figure 2 shows the results of measuring the slab temperature with a radiation thermometer during the heating time. The symbols in Figure 2 mean the same conditions as in Figure 1. The measurement point of the slab temperature was the center of one side of the slab (a position within the slab within a range of 600 to 800 mm from the edge in the width direction and 4000 to 6000 mm from the edge in the longitudinal direction). After 10 minutes had elapsed since the slab temperature reached 1320°C, the heating was stopped and the slab was extracted. During this time, the slab temperature was within the range of 1310 to 1330°C, and the extraction temperature was 1320°C. The slab was rolled and finish rolled, and then coiled to produce a hot-rolled sheet coil with a sheet thickness of 2.7 mm.
[0030] The hot-rolled sheet was then annealed at 1000°C for 60 seconds to produce a hot-rolled annealed sheet, which was then cold-rolled to a thickness of 1.8 mm and wound into a coil. The coil was passed through another coil rewinding line, and an edge roughness was detected at both ends of the coil over its entire length using a vortex-type edge roughness sensor. The detection results are shown in Table 1. As shown in Table 1, when the coil current was monotonically increased during slab heating, the number of rough edges detected increased compared to when the coil current was constant. On the other hand, it was revealed that when the coil current was monotonically decreased, the number of rough edges detected decreased compared to when the coil current was constant.
[0031] [Table 1]
[0032] Subsequently, the cold-rolled sheet was subjected to intermediate annealing at 1120°C for 80 seconds, and then subjected to secondary cold rolling to obtain a cold-rolled sheet with a final thickness of 0.22 mm. Thereafter, the cold-rolled sheet was subjected to primary recrystallization annealing by a known method to obtain a primary recrystallization annealed sheet, and then the primary recrystallization annealed sheet was subjected to secondary recrystallization annealing. Furthermore, in order to flatten the steel sheet and apply an insulating tension coating, the coil after the secondary recrystallization annealing was annealed at 830°C for 10 seconds to produce a coil of grain-oriented electrical steel sheet. The results of investigating the number of rough edges detected in the coil are shown in Table 2. The results are shown as the number of detections divided by the coil length. As in the case after cold rolling, it was found that when the coil current was monotonically decreased, the number of rough edges detected was reduced compared to the conventional constant current condition used for comparison.
[0033] [Table 2]
[0034] From the above results, it was found that the slab heating process by induction heating in hot rolling has a strong effect on the frequency of cracking at the coil edge. Furthermore, in addition to actively reviewing the slab heating conditions, the inventors have earnestly studied ways to improve the structure of the steel by optimizing each manufacturing process, which led to the invention.
[0035] Based on the above experiment 1, the following experiment was further carried out. Experiment 2 Steel material having the composition shown in Table 3 and the balance being Fe and unavoidable impurities is melted and made into a steel slab. The slab is then heated to each temperature Tr shown in Table 4 using induction heating under conditions of monotonically decreasing coil current, and held for 10 minutes in the temperature range of Tr-10℃ to Tr+10℃. After the slab is extracted at temperature Tr, the average finishing temperature of the head and tail of the hot rolled strip is 9 The hot-rolled sheet was hot-rolled to a temperature of 30°C to obtain a hot-rolled sheet having a thickness of 2.7 mm. The hot-rolled sheet thus obtained was annealed at 1000°C for 60 seconds to obtain a hot-rolled annealed sheet. The hot-rolled annealed sheet was then subjected to primary cold rolling to obtain an intermediate thickness of 1.8 mm, and further subjected to intermediate annealing at 1120°C for 80 seconds, followed by secondary cold rolling to obtain a cold-rolled sheet having a final thickness of 0.22 mm. Thereafter, the cold-rolled sheet was subjected to primary recrystallization annealing by a known method to obtain a primary recrystallization annealed sheet, and then the primary recrystallization annealed sheet was subjected to secondary recrystallization annealing to obtain a steel sheet. Furthermore, in order to flatten the steel sheet and apply an insulating tension coating, the coil after the secondary recrystallization annealing was annealed at 830°C for 10 seconds to produce a coil of grain-oriented electrical steel sheet. The number of rough edges detected in the coil was investigated, and the results are shown in Table 4.
[0036] [Table 3]
[0037] [Table 4]
[0038] The results of an experiment using Steel No. A showed that the number of rough edges detected tended to increase when the slab extraction temperature was increased to 1390°C. The inventors have speculated on the cause of this as follows: When the slab extraction temperature is high, the crystal grain size of the slab becomes coarse, and the crystal grain size of the hot-rolled sheet also tends to become coarse. The inventors' structural observations also showed that many unrecrystallized grains that were coarsely elongated in the rolling direction were observed in the hot-rolled sheet heated to a high temperature, and this unrecrystallized structure was hardly reduced even in the subsequent hot-rolled sheet annealing process. Generally, the ductility of steel increases as the crystal grain size decreases. Therefore, it is believed that the hot-rolled sheet and hot-rolled annealed sheet, which are high-temperature slab-heated materials with large grain sizes, are highly brittle, and cracks formed from the ends during rolling.
[0039] With this assumption in mind, the inventors thought that if the ductility could be increased by changing the steel composition, the number of edge cracks could be further reduced. The composition of the produced slab is shown in Table 3 above. It is known that an easy way to refine the structure of steel and increase ductility is to change the carbon content of the material. However, the carbon content of the material also has a large effect on the texture of the primary recrystallized plate, and there is a risk of impairing the magnetic properties after secondary recrystallization. Therefore, the inventors investigated refining the structure by fine-tuning the amounts of Al and N. Al and N form AlN, which is an inhibitor, and if they are precipitated in the correct amount, the amount of dissolved Al or N decreases, and the Ostwald ripening of AlN is delayed. As a result, the precipitates do not coarsen in the annealing process, coarsening of the crystal grain size is strongly suppressed, and a fine structure is maintained. The condition for the proper precipitation of Al and N is when the atomic ratio of Al and N is the same (1:1), which corresponds to an Al / N mass ratio of approximately 2.0. As shown in Table 4, when compared at a slab heating temperature of 1320°C, steels A, D and E satisfied the requirement that the number of cracks per 10 m of edge roughness (edge cracks) formed beyond 3 cm in the sheet width direction was 0.020 or less when compared at a slab heating temperature of 1320°C. In other words, it is considered that edge roughness can be effectively suppressed when the Al / N value is between 1.8 and 3.0.
[0040] Furthermore, the inventors have discovered that if the induction heating is performed while changing the frequency, and the frequency does not decrease over time, the temperature inside the slab can be made more uniform and the magnetic flux density can be made good throughout the entire length of the slab. The slab heating conditions are shown in Table 5. In order to ensure consistent heat patterns even when the frequency was changed, the coil current was adjusted, and heating was performed for approximately 15 minutes under all conditions within the range of the target extraction temperature (=1325°C) ±10°C. Note that the heating conditions were changed at 20, 30, 40, and 50 minutes after the start of heating, so the conditions before and after the change are also shown. Table 6 shows the evaluation results of edge roughness and magnetic flux density of the grain-oriented electrical steel coil manufactured using this slab.
[0041] [Table 5]
[0042] [Table 6]
[0043] The magnetic flux density was measured by SST for a total of 33 pieces, cut from test pieces measuring 300 mm in the rolling direction and 100 mm in the width direction, 11 pieces in the coil width direction × 3 rows in the rolling direction. In Table 6, the average value of the measurement results was calculated, and the average value and its standard deviation are shown in parentheses.
[0044] It was clear that heating pattern condition 2, in which the frequency was increased, showed no rough edges, and furthermore the average value and variation of the magnetic flux density was small, demonstrating particularly good characteristics. In contrast, pattern condition 3, in which the frequency was significantly decreased over time, did not show a pattern in which the current value decreased monotonically, and a large number of rough edges were detected. On the other hand, in condition 4, in which the frequency decreased but the amount of decrease was small, no significant difference was observed when compared to condition 1, in which the frequency was not changed.
[0045] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment. First, the appropriate range of the composition of the steel slab used as the raw material for the grain-oriented electrical steel sheet of the present invention and the reasons for limiting it will be described. In the following description, a numerical range expressed using "to" means a range including the numerical values written before and after "to" as the lower and upper limits.
[0046] C: 0.030~0.085mass% If the C content is less than 0.030 mass%, the grain boundary strengthening effect of C is lost, cracks occur in the slab, and manufacturing is hindered. In addition, non-uniform deformation, which is favorable for improving magnetic properties and occurs due to strain aging during rolling, is suppressed. On the other hand, if the C content exceeds 0.085 mass%, it becomes difficult to reduce the C content to 0.005 mass% or less at which magnetic aging does not occur in the primary recrystallization annealing. Therefore, the C content is set to a range of 0.030 to 0.085 mass%. The C content is preferably 0.040 mass% or more. Also, the C content is preferably 0.080 mass% or less.
[0047] Si: 2.00~4.50mass% Silicon is an important element for increasing the resistivity of steel sheet and reducing iron loss. If less than 2.00 mass% of silicon is added, these effects cannot be fully achieved. On the other hand, if the amount of silicon exceeds 4.50 mass%, the brittleness of the steel sheet increases, making rolling difficult. Therefore, the amount of silicon is set to a range of 2.00 to 4.50 mass%. The amount of silicon is preferably 2.50 mass% or more, and more preferably 3.00 mass% or more. The amount of silicon is preferably 4.50 mass% or less, and more preferably 4.00 mass% or less.
[0048] Mn: 0.03 to 0.50 mass% Mn is an element necessary for improving the hot workability of steel. In order to obtain the above effect, a Mn content of less than 0.03 mass% is not sufficient. On the other hand, if the Mn content exceeds 0.50 mass%, the magnetic flux density of the product sheet decreases. Therefore, the Mn content is set to a range of 0.03 to 0.50 mass%. The Mn content is preferably 0.05 mass% or more, more preferably 0.07 mass% or more. Moreover, the Mn content is preferably 0.20 mass% or less, more preferably 0.15 mass% or less.
[0049] Acid-soluble Al (Sol.Al): 0.005 mass% or more, less than 0.025 mass% Al plays a role as an inhibitor and is an important element for secondary recrystallization of Goss-oriented grains, and in order to exert its effect, it is necessary to add 0.005 mass% or more. On the other hand, if added excessively, not only does it excessively suppress grain growth and prevent secondary recrystallization of Goss-oriented grains, but it also forms a dense oxide film on the surface, making it difficult to control the amount of nitriding during nitriding and inhibiting decarburization. Therefore, the amount of sol.Al is suppressed to less than 0.025 mass%. The amount of sol.Al is preferably 0.007 mass% or more, more preferably 0.010 mass% or more. The amount of sol.Al is preferably 0.022 mass% or less, more preferably 0.018 mass% or less.
[0050] N: 0.0030~0.0090mass% Like Al, N acts as an inhibitor and is an important element in secondary recrystallization of Goss-oriented grains, and in order to achieve this effect, it is necessary to add 0.0030 mass% or more. On the other hand, N can cause defects such as blisters when the slab is heated, so it should be kept to 0.0090 mass% or less. A more suitable range is determined by the following Al / N ratio.
[0051] sol.Al / N is 1.7 to 3.0 N combines with Al to precipitate the inhibitor AlN. At that time, Al and N are combined at an atomic ratio of 1:1 and a mass ratio of approximately 2:1. In the present invention, the formation of fine ferrite grains is important for increasing ductility, and for this purpose, it is necessary to finely disperse the precipitates of AlN. Such precipitates coarsen during annealing through Ostwald ripening, and it is considered that the growth rate increases with the amount of dissolved Al and dissolved N. Therefore, Al and N form AlN with just the right amount of AlN at a mass ratio of 2:1, and the smaller the amount of dissolved Al and dissolved N, the finer the precipitates are maintained, and thus the finer the ferrite grains are obtained. Based on the above-mentioned experiment, the appropriate range of sol.Al / N is 1.7 to 3.0. Preferably, the lower limit of Al / N is 1.8. Also, preferably, the upper limit of Al / N is 2.5.
[0052] S: 0.0005~0.0300mass% S combines with Mn to form an inhibitor, but if the S content is less than 0.0005 mass%, the absolute amount of the inhibitor is insufficient, resulting in insufficient suppression of normal grain growth. On the other hand, if the S content exceeds 0.0300 mass%, desulfurization is incomplete during secondary recrystallization annealing, causing iron loss deterioration. Therefore, the S content is set to a range of 0.0005 to 0.0300 mass%, more preferably 0.0015 mass% or more, and even more preferably 0.0030 mass% or more.
[0053] At least one element selected from P, As, and Sb: 0.005 to 0.500 mass% each P and Sb are elements that dissolve in the base steel and act as inhibitors to enhance the selective growth of Goss-oriented grains, as well as improve the texture of the structure before secondary recrystallization, and are necessary for favorable secondary recrystallization of Goss-oriented grains. To achieve this effect, 0.005 mass% or more of each is added. However, excessive addition of these elements impairs rollability and interferes with manufacturing, so the upper limit of each is set to 0.500 mass%. More preferably, each is set to 0.020 mass% or more, or 0.150 mass% or less. As, a homologous element, can be added within the above range because it has the effect of improving magnetism. Since As is a toxic element, when As is used, it is used in combination with P and / or Sb, and more preferably in the range of As: 0.001 to 0.010 mass%. In addition, it is preferable to contain two or more elements selected from P, As and Sb within the above range, rather than containing P, As and Sb alone.
[0054] In the present invention, the balance of the steel slab other than the above-mentioned components is Fe and unavoidable impurities.
[0055] In the present invention, in order to improve the magnetic properties, the above components of the steel slab are further supplemented with Se: 0.0005 to 0.0200 mass%, Ni: 0.01 to 1.50 mass%, Cr: 0.03 to 0.50 mass%, Cu: 0.03 to 0.50 mass%, Sn: 0.005 to 0.500 mass%, Bi: 0.005 to 0.500 mass%, Mo: 0.005 to 0. It may appropriately contain one or more selected from the group consisting of Fe: 100 mass%, B: 0.0002 to 0.0025 mass%, Te: 0.0005 to 0.0100 mass%, Zr: 0.001 to 0.010 mass%, Nb: 0.001 to 0.010 mass%, V: 0.001 to 0.010 mass%, and Ta: 0.001 to 0.010 mass%.
[0056] [Manufacturing method] Next, a method for producing the grain-oriented electrical steel sheet of the present invention will be described. <Heating process> The steel material having the above-mentioned composition is melted by a conventional refining process, and then made into a steel slab by a conventional ingot casting-blooming rolling method or continuous casting method. Alternatively, a thin steel slab with a thickness of 100 mm or less may be manufactured by a direct casting method. These steel slabs are heated and held to an extraction temperature Tr of 1380°C or less, and then subjected to hot rolling. Furthermore, if the holding temperature is below the γ-phase precipitation temperature, the crystal phase becomes two-phase, the solid solution elements are concentrated in the γ-phase and α-phase, and the non-uniform steel structure remains until the next process and subsequent processes, which causes magnetic defects. Therefore, a more preferable holding temperature is a temperature range in which the γ-phase does not precipitate. Furthermore, if the slab is heated at a temperature above 1380°C, the ferrite grain size before hot rolling becomes excessively large, and a coarse unrecrystallized structure is formed in the hot-rolled sheet, which impairs the ductility of the steel and makes it easier to cause rough edges during rolling. The heating temperature of the slab is preferably 1350°C or less. On the other hand, the lower limit of Tr is not particularly limited as long as it is higher than the γ-phase precipitation temperature, but is preferably about 1200° C. The slab temperature is based on the surface temperature of the steel slab.
[0057] In actual slab heating, it is difficult to maintain the slab temperature exactly at the target uniform heating temperature. Therefore, in this invention, based on the results of temperature variations in actual operation, the relationship Tr-10℃≦T≦Tr+10℃ is satisfied for the slab extraction temperature: Tr (℃) of 1380℃ or less. It is necessary to heat the slab at the temperature T for 5 minutes or more. That is, the relational expression for the above temperature T means that ±10° C. is set as the allowable range for temperature variation. Furthermore, if the heating time at this temperature T is less than 5 minutes, the temperature unevenness in the slab formed during the temperature rise due to induction heating will not be sufficiently evened out, and the temperature may be low depending on the slab position, resulting in the inhibitor not being fully dissolved, which may lead to magnetic deterioration. More preferably, it is 10 minutes or more. There is no particular upper limit to the heating time, but since an excessively long time hinders productivity, it is preferably 60 minutes or less.
[0058] The slab heating of the present invention is performed by an induction heating method. The power frequency of the induction heating is 20 Hz or more and 1000 Hz or less. In induction heating, heat generation on the surface side of the slab becomes stronger due to the skin effect, which becomes more pronounced as the frequency increases. When only the surface layer is heated intensively, a temperature difference occurs between the inside of the slab and the surface slab temperature measured by a radiation thermometer that controls the slab temperature, and the deviation from this temperature becomes large. Therefore, in order to heat the slab uniformly, a low frequency is preferable, and the frequency is 1000 Hz or less. Preferably, the frequency is 300 Hz or less. More preferably, the frequency is 200 Hz or less. On the other hand, the frequency is 20 Hz or more in order to efficiently perform induction heating. Preferably, the frequency is 50 Hz or more. Incidentally, the above slab heating can further include gas atmosphere heating as a part of the induction heating, so long as the conditions of the induction heating satisfy the requirements of the present invention.
[0059] The current flowing through the coil during induction heating is controlled so that its average value decreases monotonically. "Monotonically decreasing" here means that the fluctuation due to variation does not increase by more than ±5% from the current value at the start of heating, and the current value just before the end of heating decreases by more than 5% from the current value at the start of heating. There may be no change in the current value until the middle of heating, but it is preferable that the current value just before the end of heating is at least 10% lower than the current value at the start of heating. In addition, although the coil current is not constant due to measurement variation and AC current, the above average value is the average value over 5 minutes.
[0060] Furthermore, in the heating process of the steel slab, it is preferable to monotonically increase the frequency of the induction heating. "Monotonically increasing the frequency" means gradually increasing the frequency so that the frequency at the end of heating is higher than the frequency at the start of heating, and it is preferable not to decrease the frequency during heating. Although the mechanism by which the characteristics are improved by gradually increasing the frequency is still unclear, the following reasons are thought to be the cause. That is, the energy emitted from a black body is proportional to the fourth power of the temperature, and this also roughly holds true when heating a slab; the higher the temperature, the more energy tends to be lost from the slab surface. Therefore, in the latter half of the slab heating, the slab temperature increases, and the heat loss from the slab surface also tends to increase. Therefore, by applying induction heating with a higher frequency in the latter half of the heating, it becomes possible to preferentially generate heat on the slab surface, which has a large heat loss, and it is believed that this will result in a more uniform temperature distribution throughout the slab.
[0061] <Hot rolling> The slab heated in this manner is then wound into a coil as a hot-rolled sheet by rough rolling and finish rolling. The thickness of the hot-rolled sheet is preferably in the range of 1.5 mm to 4.0 mm. The rolling end temperature is set to 950°C or lower at at least one of the front end and the tail end. If the rolling end temperature is high, the recrystallized structure during rolling becomes coarse, which leads to a decrease in the ductility of the steel in the subsequent process, impairing manufacturability. More preferably, the rolling end temperature is 920°C or lower. The lower limit of the rolling end temperature is not particularly limited as long as the slab can be wound into a coil as a hot-rolled sheet, but is about 850°C.
[0062] In the present invention, in order to prevent the coarsening of inhibitors, it is preferable to cool the hot-rolled sheet for 1 second or more at a cooling rate of 100° C. / second or more within 2 seconds after the end of finish rolling, and then coil the cooled hot-rolled sheet at a coiling temperature of 600° C. or less to complete the hot rolling process. More preferably, the hot-rolled sheet is cooled within 1 second after the end of finish rolling. Subsequently, after the finish rolling is completed, skin pass rolling may be performed before the hot-rolled sheet is annealed. By the skin pass rolling, the shape of the steel sheet can be corrected.
[0063] <Hot-rolled sheet annealing> Next, the hot-rolled sheet after the finish rolling or the hot-rolled sheet obtained by the above-mentioned skin pass rolling is subjected to hot-rolled sheet annealing. The soaking temperature of the hot-rolled sheet annealing is 750°C or more and 1170°C or less. The soaking time is 5 seconds or more and 90 seconds or less. If the soaking temperature is less than 750°C, the amount of diffusion of inhibitor-forming elements such as Al is insufficient, and the inhibitor does not precipitate sufficiently. In addition, if the soaking temperature is low, the strain remaining in the crystal grains elongated in the rolling direction of the hot-rolled sheet cannot be removed, making it difficult to obtain a grain-regulated primary recrystallized structure, and the growth of secondary recrystallized grains is inhibited. On the other hand, if the soaking temperature is high and exceeds 1170°C, the inhibitor goes into solution, and the amount of inhibitor that cannot precipitate increases. If the soaking time is less than 5 seconds, the inhibitor-forming elements cannot be sufficiently diffused, the inhibitor does not precipitate sufficiently, and it is difficult to obtain a primary recrystallized structure with regular grains. On the other hand, if the soaking time exceeds 90 seconds, the inhibitor precipitates coarsely, and the inhibitor cannot fully exert its effect of suppressing grain growth, and the primary recrystallized structure becomes excessively coarse, impairing manufacturability. The soaking temperature for the hot-rolled sheet annealing is preferably 850° C. or higher. On the other hand, the soaking temperature for the hot-rolled sheet annealing is preferably 1150° C. or lower.
[0064] The hot-rolled sheet annealing step preferably further includes a step of holding the temperature at 700°C or more and 900°C or less for 5 seconds or more and 180 seconds or less. In the hot-rolled sheet annealing step, AlN, which is not sufficiently precipitated in the hot-rolling step, is precipitated, but it has been found that AlN is efficiently precipitated in the above temperature range. In the present invention, the aim is to maintain high ductility by actively precipitating inhibitors and inhibiting grain growth, so that the above-mentioned additional annealing is preferable because it can further precipitate AlN. The temperature does not necessarily have to be kept in the above range, and it is sufficient to stay in the temperature range of 700°C or more and 900°C or less for 5 seconds or more and 180 seconds or less by adjusting the heating rate and cooling rate. A more preferable condition is that the temperature is 750°C or more. In addition, the time is more preferably 10 seconds or more, and more preferably 180 seconds or less.
[0065] <Cold rolling> After the hot-rolled sheet annealing, the hot-rolled sheet annealed sheet is subjected to one cold rolling or two or more cold rollings with intermediate annealing in between to obtain a cold-rolled sheet having a final sheet thickness. The soaking temperature of the intermediate annealing is preferably in the range of 900 to 1200°C. If the soaking temperature is 900°C or higher, it is possible to effectively prevent the recrystallized grains after the intermediate annealing from becoming too fine, and further, to effectively prevent the reduction of Goss nuclei in the primary recrystallized structure, thereby further improving the magnetic properties of the grain-oriented electrical steel sheet. On the other hand, if the soaking temperature is 1200°C or lower, the crystal grains do not become too coarse, and a more preferable primary recrystallized structure with regular grains can be obtained. More preferably, it is 1150°C or lower.
[0066] The cold rolling may be performed by either tandem rolling (unidirectional rolling) or reverse rolling, or may utilize a known warm rolling technique or interpass aging technique.
[0067] In addition, sheet cracks originating from rough edges have occurred when strong deformation such as cold rolling is applied. Therefore, if the rough edges at the coil ends are cut and removed prior to the first cold rolling, the frequency of sheet cracks can be significantly reduced. The cutting width is preferably 5 mm or more. On the other hand, the upper limit of the cutting width is not particularly limited, but is about 30 mm or less from the viewpoint of productivity, etc. The cutting and removal may be performed before the first cold rolling, i.e., continuously after the hot-rolled sheet is annealed in the cold rolling process or in the pre-processing line, or may be performed as an additional process in a dedicated line for processing. As for the cutting method, in addition to a mechanical trimmer, any publicly known technique such as laser cutting or water jet cutting can be applied.
[0068] The final thickness of the cold rolled sheet is preferably 0.15 mm or more from the viewpoint of reducing the rolling load, while the upper limit of the final thickness is 0.35 mm.
[0069] <Primary recrystallization annealing> The cold-rolled sheet having the final thickness is then subjected to primary recrystallization annealing. When the primary recrystallization annealing also serves as decarburization annealing, the annealing temperature is preferably in the range of 800 to 900°C from the viewpoint of rapidly advancing the decarburization reaction, and the atmosphere is preferably a moist atmosphere. Note that decarburization annealing may be performed separately from the primary recrystallization annealing. Thus, the grain-oriented electrical steel sheet according to the present invention can reduce the C content to the same level as an impurity, and can eliminate the adverse effects of C due to magnetic aging.
[0070] <Secondary recrystallization annealing> Next, the primarily recrystallization annealed sheet after the primary recrystallization annealing is subjected to secondary recrystallization annealing to obtain a grain-oriented electrical steel sheet. When particular importance is placed on the iron loss characteristics and the reduction of transformer noise, it is preferable to apply an annealing separator mainly composed of MgO to the surface (one or both sides) of a primarily recrystallized annealed sheet, dry it, and then perform secondary recrystallization annealing. Here, "mainly composed of MgO" means that the annealing separator contains 80% MgO by mass with respect to the entirety of the annealing separator. By applying the annealing separator to the surface of a primarily recrystallized annealed sheet and then performing secondary recrystallization annealing, it is possible to develop a secondary recrystallized structure highly concentrated in the Goss orientation and form a forsterite film on the steel sheet surface.
[0071] On the other hand, when the punching workability is important and the forsterite film is not formed, it is preferable to not use the annealing separator or to perform secondary recrystallization annealing using an annealing separator mainly made of silica or alumina. Here, "mainly made of silica or alumina" means that the annealing separator contains 80% by mass of silica or alumina. In addition, when the forsterite film is not formed, it is also effective to apply the annealing separator by electrostatic application that does not bring in moisture. In addition, a known heat-resistant inorganic material sheet may be used instead of the annealing separator. The heat-resistant inorganic material sheet contains, for example, silica, alumina, and mica.
[0072] As conditions for secondary recrystallization annealing, when a forsterite film is to be formed, it is preferable to hold the steel at about 800 to 1050°C for 20 hours or more to induce and complete secondary recrystallization, and then to further increase the temperature to 1100°C or higher. When placing importance on iron loss characteristics and performing purification treatment, it is preferable to further increase the temperature to about 1200°C. On the other hand, when a forsterite film is not to be formed, it is sufficient to complete secondary recrystallization, and therefore annealing can be completed by increasing the temperature to 800 to 1050°C. In addition, in the grain-oriented electrical steel sheet of the present invention, N, Al, S, and Se are diffused and released into the annealing separator or the annealing atmosphere during secondary recrystallization annealing, and therefore, their contents are all reduced compared to the components in the slab. Therefore, after secondary recrystallization annealing, the above-mentioned N, Al, S, and Se are treated as inevitable impurities in addition to those in the slab.
[0073] The secondary recrystallization annealed sheet (grain-oriented electrical steel sheet) after secondary recrystallization annealing may be washed with water, brushed, pickled, or the like to remove unreacted annealing separator adhering to the steel sheet surface. The secondary recrystallization annealed sheet may also be subjected to flattening annealing. Since secondary recrystallization annealing is usually performed in a coiled state, the coil may develop a curl. This curl may deteriorate the iron loss characteristics. By performing flattening annealing to correct the shape, it is possible to further reduce iron loss.
[0074] Furthermore, when steel sheets are used in a laminated state, it is effective to form an insulating coating on the surface of the steel sheet during the planarization annealing or before or after the planarization annealing. In particular, in order to reduce iron loss, it is preferable to form a tension-imparting coating that imparts tension to the steel sheet as the insulating coating. In addition to a method of applying a tension-imparting coating via a binder, a method of depositing an inorganic substance on the surface layer of the steel sheet by physical vapor deposition or chemical vapor deposition can be used to form the tension-imparting coating. These methods make it possible to form an insulating coating that has excellent coating adhesion and a significant iron loss reduction effect.
[0075] In order to further reduce iron loss, it is preferable to subject the grain-oriented electrical steel sheet to a magnetic domain refinement treatment. As a method for the magnetic domain refinement treatment, a method of forming grooves on the surface (front or back) of the grain-oriented electrical steel sheet (final product sheet), a method of introducing linear or dot-shaped thermal strain or impact strain by electron beam irradiation, laser irradiation, plasma irradiation, or the like, a method of etching the surface of a cold-rolled sheet that has been cold-rolled to the final sheet thickness or a steel sheet in an intermediate process to form grooves, or other known magnetic domain refinement treatment methods can be used. The production conditions other than those mentioned above can be the same as those in the ordinary methods.
[0076] The method disclosed in the present invention can suppress the formation of rough edges at the coil width direction edge portions of cold-rolled sheets and flattened annealed sheets, even in a component system that actively uses Group 15 elements such as P and Sb. As a result, compared to the conventional technology, sheet cracks originating from rough edges during sheet passing are reduced, and good manufacturability can be obtained. Specifically, the number of rough edges (edge cracks) formed beyond 3 cm in the sheet width direction per 10 m of flattened annealed sheet (steel sheet) can be reduced to 0.020 or less.
[0077] According to the present invention, it is possible to realize magnetic properties superior to those of the conventional art. That is, according to the manufacturing method of the present invention, the magnetic flux density B 8 It is possible to manufacture grain-oriented electrical steel sheets with a magnetic flux density B of 1.94 T or more and a sheet thickness of 0.35 mm or less. 8 Epstein test pieces were cut out from the grain-oriented electrical steel sheets, and the measurement was performed in accordance with the Epstein method described in JIS C2550.
[0078] The grain-oriented electrical steel sheet obtained by the present invention exhibits high magnetic flux density, and when the grain-oriented electrical steel sheet produced by the present technology is used in a transformer, not only can the energy usage efficiency be improved, but also the transformer noise can be reduced. Furthermore, the method for producing grain-oriented electrical steel sheet not only enables the high-efficiency use of electric power equipment such as transformers, but also contributes to the reduction of noise during operation caused by magnetostriction. EXAMPLES
[0079] A steel material having the composition shown in Table 7 and the balance consisting of Fe and unavoidable impurities was melted and made into a steel slab by a continuous casting method. The steel slab was slab heated under the conditions shown in Table 8, the steel slab was subjected to rough rolling to obtain a rough rolled sheet, the rough rolled sheet was subjected to finish rolling to obtain a hot rolled sheet, the hot rolled sheet was cooled, and the cooled hot rolled sheet was coiled. Here, the cooling was performed at a cooling rate of 100 ° C / sec or more for 1 to 5 seconds within 2 seconds after the end of finish rolling, and the hot rolled sheet was coiled in a temperature range of 450 to 600 ° C. Next, the hot rolled sheet was annealed to obtain a hot rolled sheet annealed sheet. The slab was heated using induction heating, and the frequency was constant or monotonically increased in the range of 50 Hz to 300 Hz. The cutting width when the coil end was cut and removed was 5 mm.
[0080] [Table 7]
[0081] [Table 8] TIFF0007662031000009.tif233128
[0082] After the hot-rolled sheet annealing, the sheet was pickled to remove the scale, and then cold-rolled twice with intermediate annealing or cold-rolled once to a sheet thickness of 0.22 mm. 2 -40vol%N 2 The primary recrystallization annealing was performed at 860°C for 120 seconds in a humid atmosphere with a dew point of 52-58°C to obtain a primary recrystallization sheet. An annealing separator mainly composed of MgO was applied to the surface of the primary recrystallization sheet, and secondary recrystallization annealing was performed at 1200°C for 50 hours. A phosphate-based insulating tension coating was then applied, baked, and flattening annealing was performed to flatten the steel strip to obtain a product sheet. Epstein test pieces were cut out from the obtained product sheet, and the magnetic flux density B was measured by the method described above. 8 was measured.
[0083] From Table 8, it can be seen that by applying the present invention, the generation of rough edges during rolling is suppressed, and a grain-oriented electrical steel sheet with excellent manufacturability is obtained.
Claims
1. C: 0.030 to 0.085 mass%, Si: 2.00 to 4.50 mass%, Mn: 0.03 to 0.50 mass%, S: 0.0005 to 0.0300 mass%, sol. Al: 0.005 mass% or more and less than 0.025 mass%, N: 0.0030 to 0.0090 mass%, and Contains at least one selected from P: 0.005 to 0.500 mass%, As: 0.005 to 0.500 mass%, and Sb: 0.005 to 0.500 mass%, or contains As: 0.001 to 0.500 mass%, and one or two selected from Sb: 0.005 to 0.500 mass% and P: 0.005 to 0.500 mass%, and sol. Al / N satisfies 1.7 to 3.0, A steel slab, the balance of which is Fe and unavoidable impurities, In a heating process in which the slab is heated by induction heating to a slab extraction temperature Tr (°C) of 1380°C or less and is held at a temperature T that satisfies the range of Tr-10°C≦T≦Tr+10°C for 5 minutes or more, the average current value flowing through the slab is monotonically decreased with the passage of heating time, and the induction heating frequency is in the range of 20 Hz to 1000 Hz, In the hot rolling in which the slab is finish-rolled to obtain a hot-rolled sheet, the rolling end temperature at at least one of the front end and the tail end of the hot-rolled sheet is set to 950°C or less, and the hot-rolled sheet is annealed by soaking at a temperature of 750°C to 1170°C for 5 seconds to 90 seconds to obtain a hot-rolled sheet annealed sheet, The hot-rolled annealed sheet is subjected to cold rolling once or twice or more with intermediate annealing to obtain a cold-rolled sheet of a final thickness, and the cold-rolled sheet is subjected to primary recrystallization annealing and then secondary recrystallization annealing. 8 A method for producing a grain-oriented electrical steel sheet having a thickness of 0.35 mm or less and an edge roughness (edge cracks) extending beyond 3 cm in the sheet width direction at the edge portions of 0.020 or less per 10 m of steel sheet length.
2. The steel slab further comprises: Se: 0.0005 to 0.0200 mass%, Ni: 0.01 to 1.50 mass%, Cr: 0.03 to 0.50 mass%, Cu: 0.03 to 0.50 mass%, Sn: 0.005 to 0.500 mass%, Bi: 0.005 to 0.500 mass%, Mo: 0.005 to 0.100 mass%, B: 0.0002 to 0.0025 mass%, Te: 0.0005 to 0.0100 mass%, Zr: 0.001 to 0.010 mass%, Nb: 0.001 to 0.010 mass%, V: 0.001 to 0.010 mass% and Ta:0.001~0.010mass% The method for producing a grain-oriented electrical steel sheet according to claim 1 , further comprising the step of:
3. The method for producing a grain-oriented electrical steel sheet according to claim 1, wherein the steel slab contains at least two selected from Sb: 0.005 to 0.100 mass%, As: 0.005 to 0.100 mass%, and P: 0.005 to 0.100 mass%.
4. The method for producing a grain-oriented electrical steel sheet according to claim 2, wherein the steel slab contains at least two selected from Sb: 0.005 to 0.100 mass%, As: 0.005 to 0.100 mass%, and P: 0.005 to 0.100 mass%.
5. 2. The method for producing a grain-oriented electrical steel sheet according to claim 1, wherein in the step of heating the steel slab, the frequency of the induction heating at the end of heating is set to be higher than that at the start of heating, and is not reduced during heating.
6. The method for producing a grain-oriented electrical steel sheet according to claim 2 , wherein in the step of heating the steel slab, the frequency of the induction heating at the end of heating is set to be higher than that at the start of heating, and is not reduced during heating.
7. The method for producing a grain-oriented electrical steel sheet according to claim 3, wherein in the step of heating the steel slab, the frequency of the induction heating at the end of heating is set to be higher than that at the start of heating, and is not reduced during heating.
8. The method for producing a grain-oriented electrical steel sheet according to claim 4, wherein in the step of heating the steel slab, the frequency of the induction heating at the end of heating is set to be higher than that at the start of heating, and is not reduced during heating.
9. The method for producing a grain-oriented electrical steel sheet according to any one of claims 1 to 8, wherein in the step of obtaining a hot-rolled sheet annealed sheet, the sheet is further held at a temperature of 700 ° C. or more and 900 ° C. or less for a time of 5 seconds or more and 180 seconds or less.
10. The method for producing a grain-oriented electrical steel sheet according to any one of claims 1 to 8, wherein the heating temperature of the steel slab is 1350°C or less.
11. The method for producing a grain-oriented electrical steel sheet according to claim 9, wherein the heating temperature of the steel slab is 1350°C or less.
12. The method for producing a grain-oriented electrical steel sheet according to any one of claims 1 to 8, wherein prior to a first cold rolling applied to the hot-rolled annealed sheet, 5 mm or more of the coil end is cut off and removed.
13. The method for producing a grain-oriented electrical steel sheet according to claim 9, wherein, prior to a first cold rolling applied to the hot-rolled annealed sheet, a coil end portion of 5 mm or more is cut off and removed.
14. The method for producing a grain-oriented electrical steel sheet according to claim 10, wherein, prior to a first cold rolling applied to the hot-rolled annealed sheet, a coil end portion of 5 mm or more is cut off and removed.
15. The method for producing a grain-oriented electrical steel sheet according to claim 11, wherein, prior to a first cold rolling applied to the hot-rolled annealed sheet, a coil end portion of 5 mm or more is cut off and removed.
16. The composition, by mass%, is as follows: Si: 2.00 to 4.50 mass%, Mn: 0.03 to 0.50 mass%, Further, the magnetic flux density B 8 A grain-oriented electrical steel sheet having a thickness of 1.94T or more and a sheet thickness of 0.35 mm or less, A grain-oriented electrical steel sheet having 0.020 or less rough edges (edge cracks) formed at edges extending beyond 3 cm in the sheet width direction per 10 m of steel sheet length.
17. The grain-oriented electrical steel sheet further comprises Ni: 0.01 to 1.50 mass%, Cr: 0.03 to 0.50 mass%, Cu: 0.03 to 0.50 mass%, Sn: 0.005 to 0.500 mass%, Bi: 0.005 to 0.500 mass%, Mo: 0.005 to 0.100 mass%, B: 0.0002 to 0.0025 mass%, Te: 0.0005 to 0.0100 mass%, Zr: 0.001 to 0.010 mass%, Nb: 0.001 to 0.010 mass%, V: 0.001 to 0.010 mass% and Ta:0.001~0.010mass% The grain-oriented electrical steel sheet according to claim 16, comprising one or more selected from the group consisting of:
18. The grain-oriented electrical steel sheet according to claim 16 or 17, wherein the grain-oriented electrical steel sheet contains As: 0.005 to 0.100 mass%, and at least one selected from Sb: 0.005 to 0.100 mass% and P: 0.005 to 0.100 mass%.
Citation Information
Patent Citations
JP1965-015644B
JP1971023820Y1
hifunsaibutsushitsuofunsaisurutamenoshindomiru
JP1976013469A
Heating method for grain oriented silicon steel slab
JP1987103322A
Electrical insulating material and its production
JP1995026156A